Learning needs and the orientation received by patients in the preoperative period of myocardial revascularization - Alcides Viana de Lima Neto; Vivianne Lima de Melo; Isabelle Pereira da Silva; Silvia Kalyma Paiva Lucena; Breno Wagner Araújo Cosme da Silva; Julliana Fernandes de Sena; Isabelle Katherinne Fernandes Costa (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To identify the learning needs and the orientations received by patients in the preoperative period of coronary artery bypass surgery (CABG). Method: Descriptive study, with a qualitative approach. Data collection took place from January to April 2021, through interviews carried out with 13 pre-operative patients admitted to the cardiovascular unit of a university hospital in Northeastern Brazil. The data was analyzed using descriptive statistics and the content of the interviews was processed in the software Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires. Next, an analysis of textual and similarity classes was carried out. Results: The learning needs that were analyzed were divided in five classes: events that precede the surgery in the hospital; instructions received about the surgery; sites and recovery time after surgery; general questions about the surgery and content for the educational resource. Patients reported needs related to the process of disease, surgical procedures, and care before and after surgery. With regard to orientation, 53.85% reported not having received any. Final considerations: The study identified that patients seldom received orientation. They need education on topics related to the process of the illness, the heart, surgical procedures, exams, care environments, risks, benefits, results, and changes in lifestyle to maintain health and quality of life.